Personality factors and residential differences in perceived quality of life of rural and urban dwellers in two communities in Ekiti State, Nigeria (2011)
"This study examined the personality correlates and residential differences in the perception of quality of life in one rural community and one urban community in Ekiti State, South West Nigeria. It is a cross sectional survey with 400 respondents drawn using accidental sampling technique from the general adult population of the two communities with a mean age of 35.9 and standard deviation of 9.6. Data was collected using a structured questionnaire made up of two validated scales (perceived quality of life &NEO- FFI personality inventory). Result of the data analysis revealed that personality factors (openness to experience, conscientiousness, agreeableness, extraversion and neuroticism) jointly predicted perceived quality of life and the overall percentage contribution was 16%, (F (5, 394) = 15.0; R=.40; R2= .16; p<.05). Meanwhile, only openness to experience significantly independently predicted perceived quality of life (β= .39, t = 8.41; <.05) while the remaining four factors did not. It was also found that urban dwellers have significantly higher perception of quality of life than rural dwellers (t = 4.10; df 398; p<.05). It is, therefore, recommended that government should facilitate rural development in terms of provision of essential amenities in order to improve the quality of life the rural dwellers. "